2017
DOI: 10.1088/1361-6463/aa53d6
|View full text |Cite
|
Sign up to set email alerts
|

The role of aquaporins in the anti-glioblastoma capacity of the cold plasma-stimulated medium

Abstract: The cold atmospheric plasma (CAP) is a promising novel anti-cancer method. Our previous study showed that the cold plasma-stimulated medium (PSM) exerted remarkable anti-cancer effect as effectively as the direct CAP treatment did. H 2 O 2 has been identified as a key anticancer substance in PSM. However, the mechanisms underlying intracellular H 2 O 2 regulation by cancer cells is largely unknown. Aquaporins (AQPs) are the confirmed membrane channels of H 2 O 2 . In this study, we first demonstrated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 62 publications
1
67
3
Order By: Relevance
“…In glioblastoma cells, down-regulation of survival and proliferation signaling networks plays a critical role in PAM-induced apoptosis [9,42,44]. Aquaporins, which transport hydrogen peroxide into the plasma membrane, are also key factors in apoptosis induction [45]. Many in vivo experiments have also demonstrated the anti-tumor effects of PAM against a variety of cancers.…”
Section: Indirect Treatment: Pammentioning
confidence: 99%
“…In glioblastoma cells, down-regulation of survival and proliferation signaling networks plays a critical role in PAM-induced apoptosis [9,42,44]. Aquaporins, which transport hydrogen peroxide into the plasma membrane, are also key factors in apoptosis induction [45]. Many in vivo experiments have also demonstrated the anti-tumor effects of PAM against a variety of cancers.…”
Section: Indirect Treatment: Pammentioning
confidence: 99%
“…We experimentally showed that relatively short‐lived reactive species (i.e., deactivated within approximately 10 min) in APP‐irradiated solution could activate transient receptor potential (TRP) channel family member(s) and induce physiologically relevant calcium (Ca 2+ ) influx, which plays key roles in many cellular processes . Regarding APP‐induced anti‐cancer effects, Yan et al reported that knockdown of aquaporin‐8 significantly inhibited the anti‐cancer capacity of APP‐irradiated medium . These reports indicate that membrane transporters, channels, and membrane receptors mediate between reactive species in APP‐irradiated solution and the evoked cellular responses, and thus are important biological target of APP‐produced reactive species.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Regarding APPinduced anti-cancer effects, Yan et al reported that knockdown of aquaporin-8 significantly inhibited the anti-cancer capacity of APP-irradiated medium. [11] These reports indicate that membrane transporters, channels, and membrane receptors mediate between reactive species in APP-irradiated solution and the evoked cellular responses, and thus are important biological target of APP-produced reactive species.…”
mentioning
confidence: 99%
“…CAP-activated media generally induce apoptosis due to ROS, RNS, and H 2 O 2 content [147]. The resultant effect, however, may be cell-specific and dependent on parameters such as the amount of aquaporins in the cell line [148].…”
Section: Use Of Cap For Tumour Treatmentmentioning
confidence: 99%